Increasing Skills of Student in Junior High School to Problem Solving in Geometry With Guided - Pardimin Pardimin; Sri Adi Widodo (Journal of Education and Learning (EduLearn), 2016)
Problem-solving skills is the ability of students to solve problems. One problem-solving model is solving the problem of Polya: (1) understand the problem, (2) create a troubleshooting plan, (3) implement plans troubleshooting, and (4) step check the answers. During this time problem-solving skills possessed by students are not satisfactory because the student in solving problems not yet using the steps systematically. So, we need a way to improve students' ability to solve problems, such as by way of providing guidance in solving a problem.